Apoyando el despliegue de procesos en el contexto de las pequeñas organizaciones software - Zambrano, Francisco; Patiño, Nelson; Pino-Correa, Francisco-José (Revista Científica, 2021)
Software process deployment is a work carried out by organizations to ensure that a process is used and followed in the development of their projects. However, most existing proposals for process deployment are abstract, hard to apply, and do not consider the time and resource limitations of small enterprises. In this article, a method to support process deployment in the context of small software organizations is introduced, based on elements of explicit knowledge internalization and change management. The proposed method has been assessed by experts, considering aspects of adaptability, understandability, and suitability of the method for use in small software organizations. From this assessment, we can conclude that the method is a lightweight proposal, its description is detailed, and it can be applied in such organizations.